Living Wages Around the World: Manual for Measurement - Richard Anker; Martha Anker (Edward Elgar Publishing, 2017)
This manual describes a new methodology to measure a decent but basic standard of living in different countries and how much workers need to earn to afford this, making it possible for researchers to estimate comparable living wages around the world and determine gaps between living wages and prevailing wages, even in countries with limited secondary data.
Keywords: 330; Development Economics; Labour Economics; Political Economy; Grundbedürfnisse; Mindestlohn; Messung; Armut; Welt